Effects of various disinfectants on the bacterial load and microbiome of broiler hatching eggs using electrostatic spray1 - M.K. Mohammadi-Aragh; J.E. Linhoss; J.D. Evans (Journal of Applied Poultry Research, 2022)
SUMMARY: Hatching egg disinfection is one method to reduce bacterial loads that can negatively impact chick health. Disinfection via electrostatic spray systems can improve chemical and water-use efficiency, however, the disinfection efficacy of these systems on hatching eggs is unknown. The objectives of this study were to 1) evaluate the disinfection efficacy of BioShield 75, bleach (Clorox), and Virocid on hatching eggs using electrostatic spray, and 2) characterize eggshell microbiome responses to the disinfectants. Hatching egg treatments consisted of BioShield 75, Virocid, 150 ppm bleach, water, and a dry control. Bacterial counts (CFUs) were measured 1 and 3 h postdisinfection (20 eggs per sampling time) and treatment reps were pooled for 16S rRNA sequencing analysis. Disinfectant type, sampling time, and their interaction affected eggshell bacteria counts (P ≤ 0.05). Virocid and BioShield 75, and bleach led to reductions in bacterial contamination by 2.66 (P < 0.0001), 2.09 (P < 0.0001), and 0.48 log10CFU/egg (P = 0.125), respectively. Average bacteria count increased after 3 h postdisinfection. Eggshell microbiome analysis indicated disinfectants reduced bacterial diversity, but populations were not different among treatment groups (P ≤ 0.05). Overall, electrostatic application of BioShield 75 and Virocid significantly lowered bacterial loads on broiler hatching eggs when compared to bleach, water, and dry controls. The superior disinfection efficacy of BioShield 75 and Virocid may be attributed to their long residual action, which inhibit bacterial recolonization.